Chronic Hepatitis E Infection Resulting in Graft Failure in a Liver Transplant Tourist - Hui-Hui Tan; Hoe-Nam Leong; Boon-Huan Tan; Lynette Lin-Ean Oon; Kiat-Hon Lim; Jason Pik-Eu Chang; Chee-Kiat Tan (Case Reports in Transplantation)
Hepatitis E, usually an acute hepatitis in the immunocompetent, has a chronic form described in immunocompromised hosts. We report the clinical course and outcome of an adult liver transplant recipient whose posttransplant period was complicated by chronic hepatitis E, Epstein-Barr virus infection, and cellular rejection of the graft.